A hybrid conceptual model for BIM in FM. Issue 4 (7th October 2019) - Hilal, Mustafa; Maqsood, Tayyab; Abdekhodaee, Amir
Abstract : Purpose: The purpose of this paper is to develop a hybrid conceptual model for building information modelling (BIM) adoption in facilities management (FM) through the integration of the technology task fit (TTF) and the unified theory of acceptance and use of technology (UTAUT) theories. The study also aims to identify the influence factors of BIM adoption and usage in FM and identify gaps in the existing literature and to provide a holistic picture of recent research in technology acceptance and adoption in the construction industry and FM sector. Design/methodology/approach: The research methodology was to first review the literature to determine how users come to accept new technologies and what leads to adoption of BIM in the construction industry and in FM and to identify gaps as the starting point for developing a conceptual framework for greater adoption of BIM in FM. Using the results from the literature review, the conceptual framework for BIM adoption in FM has been formulated. Findings: The resulting model of the current research is expected to improve our understanding of the acceptance and adoption of BIM by FM. Research limitations/implications: The research hypotheses need to be tested for validation. Future works includes survey and experts' interviews for model validation. Originality/value: This paper fulfils an identified need to study how FM come to accept and adopt BIM through the integration of TTF and UTAUT.